Community Energy Sharing Market Model Considering Flexible Resources on Demand Side - Xin AI; Limin XU (Zhongguo dianli)
A two-sided bidding mechanism considering flexible resources on the demand side is proposed for the community energy sharing market, and prosumers and consumers of distributed solar energy are included in the market. It is assumed that the agents formed by all consumers and prosumers have flexible aggregated electric vehicles (EVs) and energy storage equipment that can be used in demand response. Firstly, a robust virtual battery (VB) model is used to describe the flexibility of aggregated EVs under price incentives to achieve reliable and economic expansion of energy storage capacity. Then, agents set the optimal charging and discharging plan for the energy storage system in the community energy sharing market to reduce the cost of electricity. After that, the managed prosumers and consumers are applied in the market, and the non-cooperative game is employed by all community consumers and prosumers to calculate the spot price in the two-sided bidding market. An iterative algorithm is presented to clear the market and minimize the uncertainty of power supply and demand. Finally, ten agents in the community are taken as examples to verify the effectiveness of the VB model for describing the flexible resources on the demand side and the community energy sharing market model.